Penatalaksanaan Fisioterapi Pada Pasien Sprain Ankle Dengan Modalitas Ultrasound dan Thera-Band Exercise : Case Report - Afifah Nur Fauzani; Taufik Eko Susilo; Christine Viola (Jurnal Rumpun Ilmu Kesehatan, 2025)
Ankle sprain is a musculoskeletal injury caused by excessive stretching or tearing of the ankle ligaments. This injury often occurs in the ligament due to sudden inversion and plantarflexion movements during activities, resulting in overstretching of the ligament. Objective: aims to determine the benefits of providing theraband exercise and ultrasound in treating ankle sprain patients. Method: This research used a case report method which was carried out at Bung Karno Hospital, Surakarta by taking a sample of one of the sprain patients by observing and providing therapy for 3 sessions. Then, measurements were taken every time therapy was carried out. Results: in this study, the results obtained from the physiotherapy intervention were an increase in muscle strength, a decrease in pain, an increase in Range of Motion and an increase in functional activity. Conclusion: physiotherapy management by providing a program in the form of electrotherapy in the form of ultrasound and exercise therapy using thera-band exercise for ankle sprained patients which was carried out in 3 training sessions gave positive results with a decrease in pain, an increase in muscle strength, and an increase in Range of Motion.